Pilycoremediation of palm oil mill effluents (POME) using scenedesmus dimorphus and ciilorella vulgaris - Kamrul Fakir, Kamarudin (2014)
Phycorernediation is a new field of treating wastewater by biological approach using microalgae or macroalgae as a prime organism in conducting the treatment process. This environmental approach has been applied in municipal wastewater treatment and the result showed that it can reduce a significant amount of hazardous concentration especially nitrogen and phosphorus. Through phycoremediation process, microalgae utilize nutrients such nitrogen, phosphorus, other elements including heavy metals, for its growth to biomass through photosynthesis process same like terrestrial plant only at higher growth rate. The objective of this research is to investigate the microalgae capability and potential in the application of phycoremediation using POME as growth medium with three strains of microalgae, Scenedesmus dimorphus, Chloreila vu!gaTEs and Dunalielia sauna. Moreover, this research also investigate the optimisation of the levels of the variables of pH and light intensity using 22 factorial experiment design and the Method of Rotatable Composite Design for optimum percentage of (Chemical Oxygen Demand) COD, (Biochemical Oxygen Demand) BOD and Total Nitrogen (TN) removal. Experiment began with cultivation of inoculurns in aseptic (seed culture) and continued with cultivation using POME as growth medium. The efficiencies of microalgae in undergo phycoremediation process and optimisation of the levels of the variables was done in batch and repeated to obtain average value. Result from cultivation of three strains of microalgae using POME showed that only freshwater microalgae, S. dirnorphus and C. vulgaris had a significant growth rate compare to marine microalgae D. sauna. This can be explained because of low salinity value of POIvIIE which is not suitable for marine microalgae and impacting the growth of D. sauna directly. S. diinorphus and C. vulgaris cultivated using POME as medium growth obtained biomass growth from 0.26 to 3.4 mg U' and 0.34 to 4.4 mg U1 respectively. For nutrient removal of POME, S. dirnorphus showed a better result compare with C. vulgaris with ammoniacal nitrogen reduced more than 99.5% of initial concentration for S. diinorphus, while C. vulgaris only obtained 61.0%. The most significant finding was the ability of both microalgae to reduce COD and BOD concentration with reduction of 86% and 50.5% for COD reduction and 86.5% and 61.6% for BOD concentration of Scenedesmus dirnorphus and Chlorella vulgaris, respectively. For optimisation of variables levels of pH value and light intensity, result showed that percentage of COD, BOD and TN removal was achieved at 84.26%, 80.62% and 75.40% respectively at pH ranging from 6.02 to 6.53 and light intensity was 3162 lux to 3888 lux. Theorotically at same pH and light intensity, COD, BOD and TN removal was predicted at 86.18%, 81.75% and 79.20%, respectively. Characterization of biomass produced from phycoremdiation process showed that S. dimorphus produced chlorophyll a, b and carotenoid around 0.2638-0.1811, 0.0831-0.0543 and 0.1792-0.146 mgU' respectively, and C. vulgaris produced 0.1034-0.0163, 0.064-0.0115 and 00.0751-.0112 mgU'respectively. Result from this work concluded that microalgae has a big potential in application of wastewater treatment especially in reducing COD and BOD concentration of POME which can contribute to more clean and sustainable way of POME wastewater treatment. Furthermore, production of pigment from biomass produced through phycoremediation process adds more value to the treatment process and can be exploited for production of high value pigment and energy source like biodiesel.